Program Pelatihan, Pengelolaan, dan Pendampingan Sistem Filtrasi Air Danau Sentani di Kampung Hobong, Distrik Sentani - Alfred B Alfons; Bambang Suhartawan; Tanwir Tanwir; Desty Tappi; Asrul Asrul (Jurnal Medika: Medika, 2025)
This community empowerment program aimed to optimize the role of Youth Organizations (Karang Taruna) in providing safe drinking water in Hobong Village, Sentani District, Jayapura Regency through the implementation of sustainable lake water filtration technology. The implementation method used a participatory approach with stages of socialization, technical training, gradual filtration technology application, and intensive mentoring to 20 Youth Organization members as system operators. Laboratory test results showed that 6 out of 10 Lake Sentani water quality parameters did not meet quality standards, with Total Suspended Solids (83 mg/L), Total Coliform (1,100 CFU/100 mL), and E. coli (233 CFU/100 mL) exceeding clean water standards. The developed filtration system using Biofoam, Polypropylene, Chlorine Taste and Odor, Granular Activated Carbon media, and ultraviolet disinfection with a capacity of 1,000 liters/day successfully improved water quality significantly, where all parameters met the standards of Government Regulation No. 22 of 2021 with TSS removal efficiency reaching 79.5%. This program provided economic impacts in the form of cost savings of IDR 273 million per year for 175 households and social impacts through strengthening the role of youth as agents of change in communal water resource management. Community participation rates reached 95% in training, demonstrating the effectiveness of local organization-based empowerment approaches that can be replicated in other villages around Lake Sentani to improve access to safe and sustainable drinking water.